2004
DOI: 10.1002/jbm.a.30134
|View full text |Cite
|
Sign up to set email alerts
|

1α,25(OH)2D3 Regulation of integrin expression is substrate dependent

Abstract: Osteoblasts are attachment-dependent cells that interact with their surface through integrin-mediated mechanisms. Their differentiation is regulated by 1,25-dihydroxyvitamin D3 [1alpha,25(OH)(2)D(3)] and is affected by substrate chemistry and microtopography, suggesting that 1alpha,25(OH)(2)D(3) may regulate integrin expression in a surface-specific manner. To test this hypothesis, osteoblast-like human MG63 cells were grown on tissue culture plastic and on grit-blasted and acid-etched titanium disks with a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 50 publications
4
39
0
1
Order By: Relevance
“…We previously noted that MG63 cells exhibit increased expression of ␣2 and ␤1 but not ␣5 when cultured on Ti compared with TCPS (43). Here, we report that microstructure can modulate ␣2 and ␤1 expression and that surface energy also plays a regulatory role.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We previously noted that MG63 cells exhibit increased expression of ␣2 and ␤1 but not ␣5 when cultured on Ti compared with TCPS (43). Here, we report that microstructure can modulate ␣2 and ␤1 expression and that surface energy also plays a regulatory role.…”
Section: Discussionmentioning
confidence: 53%
“…In contrast, antibodies to ␣2␤1 reduced osteoblast differentiation, suggesting a role for ␣2. Moreover, ␤1 and ␣2 mRNAs were increased when osteoblasts were grown on Ti substrates rather than TCPS, whereas ␣5 expression was unaffected (43). 1␣,25(OH) 2 D 3 further increased ␣2 and ␤1 mRNAs in cells cultured on Ti, but had no effect on ␣5.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Because integrins signal through some of the same pathways as 1α, 25(OH) 2 D 3 , cross talk is possible. We found that mRNA levels for integrin subunits beta-1 (β 1 ), alpha-2 and alpha-5, but not for alpha-v or beta-3, were affected by substrate roughness and that the effects were specific to each subunit and varied with time in culture [14]. 1α,25 (OH) 2 D 3 modulated levels of β 1 and the effects were greater on the rougher surface.…”
Section: Role Of Integrinsmentioning
confidence: 89%
“…Studies examining the contribution of surface micro-roughness show that differences in surface topography, including roughness, affect fibronectin and albumin adsorption in vitro [5], and growth of fibroblasts and osteoblast-like cells in culture [6]. Sandblasted Ti supports stronger osteoblast adhesion [7,8], related at least in part to altered integrin expression, higher focal contact density and reorganized cytoskeleton of cells on the rough surface [9]. Cells cultured on microrough Ti surfaces also exhibit decreased proliferation and increased differentiation [8,10].…”
Section: Introductionmentioning
confidence: 99%